Emotions Vocabulary and the Reconceptualisation of Emotions in Ann Radcliffe’s "The Italian, or the Confessional of the Black Penitents" - Andonova-Kalapsazova, Elena D. (English Studies at NBU, 2019)
The article undertakes the analysis of Ann Radcliffe’s novel The Italian, or the Confessional of the Black Penitents (1797) from a history of literary emotions perspective which, I argue, yields insights into the attitudes towards emotions embedded in Radcliffe’s works. A reading of the novel from such a perspective also complements the critical studies of the artist’s engaging with the eighteenth-century cult of sensibility. The novel is read as a text that registered but also participated in the dissemination of an epistemology of emotional experience articulated in the idiom of eighteenth-century moral philosophers - Francis Hutcheson, David Hume and Adam Smith - at the same time as it retained some of the older, theology-based conceptions of passions and affections. The dynamic in which the two frameworks for understanding the emotions exist in the novel is explored through a close reading of the vocabulary in which Radcliffe rendered the emotional experiences of her fictional characters. In this reading it is the passions which are found to have been invested with a variety of meanings and attributed a range of moral valences that most noticeably foreground the movement from a generally negative towards a more complex appreciation of powerful emotions.